SHORT REVIEW ON RENEWABLE ENERGY POLICY AND ENERGY CONSUMPTION OF BUILDINGS IN MALAYSIA - Chan, Nicole; Go, Tze Fong; chong, perk lin; Moey, Lip Kean; Chia, Chee Ming (Journal of Engineering & Technological Advances, 2022)
The energy generation sector has contributed a large percentage of greenhouse gases (GHG) emissions in Malaysia. Carbon dioxide emissions from the burning of traditional energy source like fossil fuels to meet the ever-growing demand for electricity contributes to global warming. Therefore, transitioning into a greener and more sustainable energy alternative has been a priority to the government and stakeholders. As Malaysia is a developing country, renewable energy development is growing relatively at a slow pace and therefore public and private sectors are taking initiatives as well to reduce electricity consumption. A case study was done on public higher institutions in Malaysia to analyze electricity consumption by comparing the building energy index (BEI) with the standards proposed by MS1525. This paper also includes a brief summary of practices and strategies done by buildings in Malaysia to promote energy efficiency and reduce electricity consumption that can be used as an example and implemented by others to incorporate energy efficient practices. With the participation of all stakeholders, we are able to create a future with a more sustainable energy source and reduce the dependency on fossil fuels.